Association Between Glycemic Gap and In-hospital Outcomes in Aneurysmal Subarachnoid Hemorrhage - Sun, Philip Y.; Poblete, Roy A.; Nguyen, Peggy L.; Bulic, Sebina F.; Kim-Tenser, May A.; Marehbian, Jonathan; Cen, Steven Y.; Emanuel, Benjamin A. (Frontiers in Neurology, 2021)
Introduction: Glycemic gap (GG), as determined by the difference between glucose and the hemoglobin A1c (HbA1c)-derived estimated average glucose (eAG), is associated with poor outcomes in various clinical settings. There is a paucity of data describing GG and outcomes after aneurysmal subarachnoid hemorrhage (aSAH). Our main objectives were to evaluate the association of admission glycemic gap (aGG) with in-hospital mortality and with poor composite outcome and to compare aGG’s predictive value to admission serum glucose. Secondary outcomes were the associations between aGG and neurologic complications including vasospasm and delayed cerebral ischemia following aSAH. Methods: We retrospectively reviewed 119 adult patients with aSAH admitted to a single tertiary care neuroscience ICU. Spearman method was used for correlation for non-normality of data. Area under the curve (AUC) for Receiver Operating Characteristic (ROC) curve was used to estimate prediction accuracy of aGG and admission glucose on outcome measures. Multivariable analyses were conducted to assess the value of aGG in predicting in-hospital poor composite outcome and death. Results: Elevated aGG at or above 30mg/dL was identified in 79 (66.4%) of patients. Vasospasm was not associated with the elevated aGG. Admission GG correlated with admission serum glucose (r=0.94, p<0.01), lactate (r=0.41, p<0.01), procalcitonin (r=0.38, p<0.01), and Hunt and Hess score (r= 0.51, p<0.01), but not with HbA1c (r=0.02, p=0.82). Compared to admission glucose, aGG had a statistically significantly improved accuracy in predicting inpatient mortality (AUC mean±SEM: 0.77±0.05 vs. 0.72±0.06, p=0.03) and trended towards statistically improved accuracy in predicting poor composite outcome (AUC: 0.69±0.05 vs. 0.66±0.05, p=0.07). When controlling for aSAH severity, aGG was not independently associated with delayed cerebral ischemia, poor composite outcome, and in-hospital mortality. Conclusion: Admission GG was not independently associated with in-hospital mortality or poor outcome in a population of aSAH. An aGG ≥30mg/dL was common in our population, and further study is needed to fully understand the clinical importance of this biomarker.